The Impact of Communication on Conflict between Expatriate and Local Managers Working in NPD Projects of MNC Subsidiaries: A Local Perspective. Issue 1 (2nd January 2016) - Darawong, Chonlatis; Igel, Barbara; Badir, Yuosre F.
ABSTRACT: This study investigates the impact of communication between expatriate and local managers on two types of conflict in subsidiaries of multinational companies (MNCs) engaged in new product development (NPD). The data was collected from 438 local NPD managers who regularly collaborate and communicate with expatriate managers. The findings suggest that the quality and bidirectionality of cross-cultural communication reduce relationship conflict but increase task-related conflict. In addition, a more formalized communication style increases both relationship conflict and task conflict. The findings hold implications for MNCs in that improvements to different communication dimensions are suggested.